2007
DOI: 10.4049/jimmunol.178.8.4803
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells from Lupus-Prone Mice Are Defective in Repressing Immunoglobulin Secretion

Abstract: Autoimmunity results from a breakdown in tolerance mechanisms that regulate autoreactive lymphocytes. We recently showed that during innate immune responses, secretion of IL-6 by dendritic cells (DCs) maintained autoreactive B cells in an unresponsive state. In this study, we describe that TLR4-activated DCs from lupus-prone mice are defective in repressing autoantibody secretion, coincident with diminished IL-6 secretion. Reduced secretion of IL-6 by MRL/lpr DCs reflected diminished synthesis and failure to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…1b). Defects in DC/MΦ-mediated repression are coincident with diminished secretion of IL-6 and sCD40L and failure to sustain IL-6 mRNA production and activation of the IκB/NFκB pathways [107]. Similarly, we found that IL-6 and sCD40L fail to repress B cells from lupus-prone mice (unpublished data).…”
Section: Arresting and Silencing Sm-specific B Cellsmentioning
confidence: 76%
See 1 more Smart Citation
“…1b). Defects in DC/MΦ-mediated repression are coincident with diminished secretion of IL-6 and sCD40L and failure to sustain IL-6 mRNA production and activation of the IκB/NFκB pathways [107]. Similarly, we found that IL-6 and sCD40L fail to repress B cells from lupus-prone mice (unpublished data).…”
Section: Arresting and Silencing Sm-specific B Cellsmentioning
confidence: 76%
“…Decreased clearance of apoptotic cells and defects in phagocytosis by MΦs in SLE patients and lupus-prone mice may lead to autoimmunity [69,108,[122][123][124]. The increase in apoptotic cells and antigens could dysregulate DCs and MΦs, triggering a chronic anti-inflammatory response that downregulates the production of cytokines important for B cell tolerance [45,107].…”
Section: Apoptotic Cells: Dangerous In Deathmentioning
confidence: 99%
“…Likewise, defects in MRL/lpr DCs are associated with the MRL background. 28 These data indicate that M⌽s regulate autoreactive B cells by secreting repressive factors that inhibit the formation of ASCs. This mechanism of tolerance is diminished in lupus-prone mice, suggesting its role in the autoimmunity associated with SLE.…”
Section: Discussionmentioning
confidence: 95%
“…A second mechanism was defined in the Sm-specific model, in which dendritic cells (DCs) and macrophages selectively repress antibody production by self-reactive B cells but not naive B cells 53 . Repression is partly mediated by soluble factors, such as interleukin-6 (IL-6) and soluble CD40 ligand (CD40L), secreted by activated DCs and macrophages, and by an ill-defined, contact-dependent mechanism [53][54][55] . So, chronic binding of self antigen may reprogram IL-6 receptor and CD40 signalling, leading to alternative outcomes in autoreactive B cells.…”
Section: Effects Of Innate Immune Signalsmentioning
confidence: 99%